A Randomized Clinical Study (SEECASE) to Assess Efficacy, Safety, and Tolerability of NOV03 for Treatment of Dry Eye Disease. Issue 9 (September 2021) - Tauber, Joseph; Wirta, David L.; Sall, Kenneth; Majmudar, Parag A.; Willen, Daniela; Krösser, Sonja
Abstract : Purpose: NOV03 has a unique dual mode of action to address dry eye disease (DED) associated with meibomian gland dysfunction. SEECASE evaluated the efficacy, safety, and tolerability of NOV03 at 2 dosing regimens compared with a saline comparator in patients with DED. Methods: SEECASE was a prospective, multicenter, randomized, double-masked, saline-controlled clinical study. A total of 336 DED patients [tear film breakup time ⩽5 seconds, abnormal meibum secretion, total corneal fluorescein staining (tCFS) score of 4 ⩽ X ⩽ 11 (National Eye Institute scale), Schirmer of ≥5 mm] were randomized in a 2:2:1:1 manner to NOV03 4 times daily (QID), NOV03 twice daily (BID), saline BID, and saline QID, respectively. The primary efficacy endpoint was tCFS staining at 8 weeks for both regimens. Secondary endpoints included visual analog scales and the Ocular Surface Disease Index questionnaire for symptom assessment. Results: The study met its primary endpoint, change from baseline of tCFS over control, for both dosing regimens QID and BID ( P < 0.001 and P = 0.009, respectively). NOV03 also showed pronounced improvement in various symptoms. For the Eye Dryness Score, changes from baseline were statistically significant compared with those of the control at week 8 [ P < 0.001 (QID) and P = 0.002 (BID)]. Benefits on tCFS and symptoms started at 2 weeks after start of treatment and were maintained over the study duration. The effects were dosing schedule dependent. NOV03 was well tolerated with instillation site reactions below 3% in both treatment regimes. Conclusions: The SEECASE study demonstrated that NOV03 improves signs and symptoms in patients with highly symptomatic evaporative dry eye disease.